KEPADATAN POPULASI Spodoptera exigua (Lepidoptera: Noctuidae) PADA BAWANG MERAH DI KAMPUNG BATU KECAMATAN DANAU KEMBAR KABUPATEN SOLOK - Yuliana, Dice; Jasmi, Jasmi; Safitri, Elza (Pendidikan Biologi, 2013)
ABSTRACTÂ The population caterpillar onions ( Spodoptera exigua ) on red onion can reduce onion yield . In connection with the matter has done research on the population density of Spodoptera exigua ( Lepidoptera : Noctuidae ) on red onion in Kampung Batu kecamatan danau kembar kabupaten solok which aims to determine the population density of Spodoptera exigua on red onion in Kampung Batu kecamatan danau kembar kabupaten solok.This research was conducted in August-September 2013, with a descriptive survey method is by way of direct collection of the larvae of Spodoptera exigua existing research the location. Field sampling conducted on red onion age of 4 weeks and 6 weeks after planting. Physical environmental factors measured the temperature and humidity. Widely used as a study area of about 30 x 20 m.The results were obtained an average population density of Spodoptera exigua on shallot in Kampung Batu kecamatan danau kembar kabupaten solok was 4.05 individuals / plant. Spodoptera exigua population densities are found already crossed the threshold of pest control.Â Â